Efektivitas Program Pelatihan Kerja di Kantor Latihan Ker- ja (KLK) Kabupaten Mandailing Natal Perspektif Ekonomi Islam - Siti Kholijah (Jurnal AL-AHKAM, 2019)
The increase in unemployment in Mandailing Natal Regency is caused by a mismatch between the qualifications of the workforce requested by the com- pany, the type of position and placement location that is less attractive to job seekers, and less competency of workers according to available positions. The Work Training Office (KLK) of Mandailing Natal Regency as one of the agen- cies that provide public services in the field of employment is expected to pro- vide easy information services, provision of facilities, and implement programs that support their careers in the future. The low quality of labor in Mandailing Natal District is a barrier to economic development. This is due to the low level of education and the level of knowledge of the workforce, making it difficult to find work that demands the quality of reliable human resources. Especially in the era of globalization, workers who do not have quality will have difficulty competing with those who already have quality. In this competition, it is certain that workers who do not have quality will be excluded. To improve the quality of the workforce, the City Government of Mandailing Natal District through the Mandailing Natal District Work Training Office (KLK) organized a job training program. The work training program at the Mandailing Natal District Training Office (KLK) involves the community as the main target that must be maximally empowered. This Papaer examines the effectiveness of work train- ing programs that have been implemented in improving human resources and especially in reducing unemployment in Mandailing Natal District.